Os produtos educacionais de química desenvolvidos por mestrados profissionais em ensino de ciências no Brasil - Cavalcante, Dafne Alexandre (2015)
The pursuit of excellence in teaching chemistry in Brazil is reflected in the growing interest of the academic community to develop work in this area. This dissertation aims to study the academic production of Master Professionals with the trends of the current teaching on developing various skills and competencies of students of chemistry. A literature search was performed to survey the educational products in the field of chemistry developed in Master Professional Programs until 2013. This data was conducted by collecting information related to educational products, elaborated on Institutions of Higher Education, from information available in Portal da Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES) and the electronic addresses of Programs Professional Master, which have the area of education in chemistry. The development of educational products in various locations in Brazil promotes positive changes in teaching practices. The results show a quantitative 29 institutions that have the field of chemistry in their Professional Master Programs. Among these institutions, nine have 105 educational products developed in that area. The study researchers observed improvements in teaching and learning. Information concerning these products were on a CD-ROM. They are Educational Media (18%), Proposals for Teaching (36%), Textual Material (39%), Materials Interactives (4%) and Extension Activities (3%). This can improve educational practices in chemistry classes through access to those products or stimulus to create new activities, improving the quality of education.